METODE PEMBELAJARAN SAINS DALAM PERSPEKTIF PENDIDIKAN ISLAM - Suardi Ishak (Universitas Islam Negeri Ar-Raniry, 2015)
Secularization of science and technology with religious values have been wrapped so neatly by the nature of Western thoughts which is then transmitted to the various facets of life including general education. Secular science claim to be objective, value-free, and free of other interests, including religion. Even science has been positioned as a replacement for the position of Allah’s revelation (Qur'an) as a hint of modern life. Islam considers rational sciences are supporting the implementation of worship that are mahdah. Islam considers that the source of knowledge is a revelation, a revelation further demands that humans use ratio for the development of the verses kauniyah and 'am. The results show that Al-Attas view that science is the result of engineering and development ratio. Basic resource (nas) does not see the dualism between secular science with hereafter science, but the results of ijtihad is man who produce various schools and understand the science that led to varying perspectives. Secularism, atheism and others led to the development of science adapted to the mindset of developers. At-Attas view that science serves to carry out the obligations both to Allah and to mankind is mandatory required and held as well, and vice versa. Various development science and science must be in a way or means to carry out worship.